Memory on the move. - Sherwin, R.M (IEEE spectrum)
The author describes how, competing for the US 11 billion dollars portable electronic device memory market are several venerable but revitalized memory systems as well as new storage technologies: flash memory cards; PC memory cards; and small disk drives. Flashers, a relatively young technology contain one or more nonvolatile solid-state memory chips. They have no moving parts and retain data in the absence of power. Like these, but an industry unto itself, is the PC Card; now almost 10 years old, the business-card-sized memory and application device is heavily used to add functions to mobile computers. The spinners are a completely upgraded group of rotating disk drive systems based on both magnetic and optical technologies